Cross-ancestral GWAS identifies 29 variants across head and neck cancer subsites - Ebrahimi, Elmira; Sangphukieo, Apiwat; Park, Hanla A; Gaborieau, Valerie; Ferreiro-Iglesias, Aida; Diergaarde, Brenda; Ahrens, Wolfgang; Alemany, Laia; Arantes, Lidia Mrb; Betka, Jaroslav; Bratman, Scott V; Canova, Cristina; et al. (Nature communications, 2025)
Head and neck squamous cell carcinoma (HNSCC) includes diverse cancers arising in the oral cavity, oropharynx, and larynx, with the main risk factors being environmental exposures such as tobacco, alcohol, and human papillomavirus (HPV) infection. The genetic factors contributing to susceptibility across different populations and tumour subsites remain incompletely understood. Here we show, through a genome-wide association and fine mapping study of over 19,000 HNSCC cases and 38,000 controls from multiple ancestries, 18 genetic risk variants and 11 signals from fine mapping of the human leukocyte antigen (HLA) region, all previously unreported. rs78378222, a regulatory variant for TP53 is associated with a 40% reduction in overall HNSCC risk. We also identify gene-environment interactions, with BRCA2 and ADH1B variants showing effects modified by smoking and alcohol use. Subsite-specific analysis of the HLA region reveals distinct immune-related associations across HPV-positive and HPV-negative tumours. These findings refine the genetic architecture of HNSCC and highlight mechanisms linking inherited variation, immunity, and environmental exposures.
Keywords: Alcohol Drinking; studie případů a kontrol; pití alkoholu; Humans; Genetic Predisposition to Disease; genetická predispozice k nemoci; lidé středního věku; nádory hlavy a krku; Middle Aged; kouření; celogenomová asociační studie; infekce papilomavirem; dlaždicobuněčné karcinomy hlavy a krku; Carcinoma, Squamous Cell; Papillomavirus Infections; Smoking; Risk Factors; mužské pohlaví; spinocelulární karcinom; Tumor Suppressor Protein p53; HLA Antigens; Squamous Cell Carcinoma of Head and Neck; nádorový supresorový protein p53; alkoholdehydrogenasa; rizikové faktory; BRCA2 Protein; Alcohol Dehydrogenase; ženské pohlaví; interakce genů a prostředí; Female; Gene-Environment Interaction; jednonukleotidový polymorfismus; lidé; Polymorphism, Single Nucleotide; Case-Control Studies; Head and Neck Neoplasms; Genome-Wide Association Study; Male; HLA antigeny; protein BRCA2